A dynamic model of classifier competence based on the local fuzzy confusion matrix and the random reference classifier - Trajdos, Pawel; Kurzynski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
Nowadays, multiclassifier systems (MCSs) are being widely applied in various machine learning problems and in many different domains. Over the last two decades, a variety of ensemble systems have been developed, but there is still room for improvement. This paper focuses on developing competence and interclass cross-competence measures which can be applied as a method for classifiers combination.
Keywords: multiclassifier; cross-competence measure; confusion matrix; feedback information